Reach the Highest Standard in Professional Learning : Leadership. - Louis, Karen Seashore (SAGE Publications, 2016)
Make your school a place where professional learning thrives This volume, part of Learning Forward's series on its seven Standards for Professional Learning, shows school leaders how to orchestrate a learning environment that empowers teachers to take charge of their own development. Features include: An original essay by Karen Seashore Louis on creating a school culture where all adults are part of the enterprise of continuous learning Strategies, tools, and examples focused on the leader's role in promoting professional learning A case study of one district's success in improving outcomes fo.